CompTIA security+ : review guide - Stewart, James Michael (Serious skills., 2011)
Reinforce your preparation for CompTIA's new Security+ exam with this focused review toolBefore you take CompTIA's new Security+ exam SY0-301, reinforce your learning with a thorough review and lots of practice. The new edition of this review guide helps you do just that. It covers all six domains of exam SY0-301 and all exam objectives, and it includes a helpful "Exam Essentials" section in each chapter to help you zero in on what you need to know. A companion CD offers additional study tools, including two complete practice exams, over a hundred electronic flashcards, and more. Reviews and reinforces the material you need to know for CompTIA's new Security+ exam SY0-301 Covers all exam objectives and the six domain areas of the Security+ exam: Network Security; Compliance and Operational Security; Threats and Vulnerabilities; Application, Data and Host Security; Access Control and Identity Management; and Cryptography Helps you drill and prepare with over 120 review questions, two practice exams, over 100 electronic flashcards, and more on a companion CD Goes hand in hand with any learning tool, including Sybex's CompTIA Security+ Study Guide, 5th Edition Earn your Security+ certification, then use it as a springboard to more difficult certifications. Start by acing exam SY0-301 with the help of this practical review guide!"